2016
DOI: 10.1121/1.4966677
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in the perception of regional, nonnative, and disordered speech varieties

Abstract: Speech perception abilities vary substantially across listeners, particularly in adverse conditions including those stemming from environmental degradation (e.g., noise) or from talker-related challenges (e.g., nonnative or disordered speech). This study examined adult listeners' recognition of words in phrases produced by six talkers representing three speech varieties: a nonnative accent (Spanish-accented English), a regional dialect (Irish English), and a disordered variety (ataxic dysarthria). Semantically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
64
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(79 citation statements)
references
References 34 publications
14
64
1
Order By: Relevance
“…Previous research indicated that listeners use additional cognitive, linguistic, and/or perceptual resources for speech perception under adverse conditions (Heinrich, Schneider, & Craik, 2008;Pichora-Fuller, Schneider, & Daneman, 1995;Rabbitt, 1968), and that individuals vary substantially in their ability to perceive speech in adverse listening conditions (e.g., Benichov et al, 2012;Bent et al, 2016;Wightman et al, 2010). Skills such as auditory working memory, receptive vocabulary, inhibition, and rhythm perception have been investigated as indicators of aptitude in the perception of environmentally degraded or accented speech.…”
Section: Cognitive Linguistic and Perceptual Resourcesmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous research indicated that listeners use additional cognitive, linguistic, and/or perceptual resources for speech perception under adverse conditions (Heinrich, Schneider, & Craik, 2008;Pichora-Fuller, Schneider, & Daneman, 1995;Rabbitt, 1968), and that individuals vary substantially in their ability to perceive speech in adverse listening conditions (e.g., Benichov et al, 2012;Bent et al, 2016;Wightman et al, 2010). Skills such as auditory working memory, receptive vocabulary, inhibition, and rhythm perception have been investigated as indicators of aptitude in the perception of environmentally degraded or accented speech.…”
Section: Cognitive Linguistic and Perceptual Resourcesmentioning
confidence: 99%
“…Receptive vocabulary Behavioral studies examining multiple types of challenging listening conditions have found relationships between receptive vocabulary and the intelligibility of disordered speech as well as of speech with unfamiliar accents (Banks, Gowen, Munro, & Adank, 2015;Bent et al, 2016;Janse & Adank, 2012). For example, Janse and Adank investigated listeners' perceptual adaptation to a novel constructed accent in both auditory-only and audiovisual presentations, and compared adaptation with the listeners' cognitive abilities.…”
Section: Cognitive Linguistic and Perceptual Resourcesmentioning
confidence: 99%
See 1 more Smart Citation
“…In young adults, an increase in vocabulary size was associated with better listening comprehension (Andringa et al, 2012). Large vocabulary size was also found to be linked to better speech recognition in suboptimal conditions (Bent et al, 2016). Furthermore, Yap et al (2012) found higher vocabulary scores to be associated with more accurate and faster word recognition in lexical decision and speeded pronunciation tasks.…”
Section: Introductionmentioning
confidence: 99%
“…That is, while the exact structure of non-native speech may provide some unique challenges, it is not the case that we should claim that nonnative speech is perceived in an entirely different way than native speech. In fact, in a growing body of work, researchers have demonstrated that there are substantial similarities in the types of cognitive skills that underlie the perception of different types of unfamiliar speech (e.g., dysarthric speech, an unfamiliar native accent, and non-native speech; Bent, Baese-Berk, Borrie, & McKee, 2016;McLaughlin, BaeseBerk, Bent, Borrie, & Van Engen, 2018). These results suggest that rather than treating non-native speech as a special case of speech perception that does not need to be accounted for by general models of speech perception, it instead provides a unique and convenient tool for better defining our models and theories of speech perception.…”
Section: Discussionmentioning
confidence: 99%